Religious Evidentialism - Dormandy, Katherine (European journal for philosophy of religion, 2013)
Should religious believers proportion their religious beliefs to their evidence? They should: religious faith is better, ceteris paribus, when the beliefs accompanying it are evidence-proportioned. I offer two philosophical arguments and a biblical argument. The philosophical arguments conclude that love and trust, two attitudes belonging to faith, are better, ceteris paribus, when accompanied by evidence-proportioned belief, and that so too is the faith in question. The biblical argument concludes that beliefs associated with faith, portrayed in the Hebrew bible and the New Testament, are typically, and normatively, exhorted on the basis of evidence. I hope to convince religious believers and nonbelievers alike that religious beliefs should be evidence-proportioned.